Rabi pulses: multiple security and prosperity - Krishna, Bal; Kumar, Rakesh; Kumar, Birender; Choudhary, Jaipal (Indian Farming, 2022)
Crop diversification, including the adoption of rabi pulses, can help Indian agricultural production systems to be more sustainable. Pulses, in particular, are crops that can assist both agriculture and the food industry to become more eco-friendly by reducing greenhouse gas emissions and absorbing more carbon. Lock-in has hampered the development of minor crops today, as main crops have been co-developed to a greater level in farming and food production systems. All of these characteristics make pulse-based farming systems ideal candidates for climate-resilient crops.